The Phoenician Shipwreck off Xlendi Bay, Gozo – initial observations, size and shipbuilding technologies used - Bravo-Morata Rodríguez, Alberto; Gambin, Timmy (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In 2007, during an offshore remote sensing survey aimed at mapping Malta’s Underwater Cultural Heritage, a small anomaly was noted in the sonar data. Since then, a team led by the University of Malta has been studying what turned out to be an extremely important discovery. Found at a depth of 110 m off Xlendi Bay in Gozo (Malta), the Phoenician shipwreck consists of an intact and well-preserved mixed cargo of amphoras, saddle querns and grinding stones datable to the 7th century BC. The paper focuses on a particular aspect of the site – the ship itself. Using the limited evidence available so far, the authors present aspects related to the site’s size, the wood used for its construction as well as construction techniques.